2017
DOI: 10.1038/s41598-017-03107-y
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic evidence that both ancient vicariance and dispersal have contributed to the biogeographic patterns of anchialine cave shrimps

Abstract: Cave shrimps from the genera Typhlatya, Stygiocaris and Typhlopatsa (Atyidae) are restricted to specialised coastal subterranean habitats or nearby freshwaters and have a highly disconnected distribution (Eastern Pacific, Caribbean, Atlantic, Mediterranean, Madagascar, Australia). The combination of a wide distribution and a limited dispersal potential suggests a large-scale process has generated this geographic pattern. Tectonic plates that fragment ancestral ranges (vicariance) has often been assumed to caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 58 publications
(94 reference statements)
2
56
0
Order By: Relevance
“…The use of mitochondrial genomes for phylogenetics in metazoans, including crustaceans, has exploded in recent years due to the advances experienced in genomic techniques 24 . Although the usefulness of mitochondrial sequences as a sole genetic marker has been questioned 25 , they are still widely used in phylogenetic inference, species delimitation or identification and, in conjunction with nuclear multilocus data, to detect mito-nuclear discrepancies derived from hybridization/introgression events 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of mitochondrial genomes for phylogenetics in metazoans, including crustaceans, has exploded in recent years due to the advances experienced in genomic techniques 24 . Although the usefulness of mitochondrial sequences as a sole genetic marker has been questioned 25 , they are still widely used in phylogenetic inference, species delimitation or identification and, in conjunction with nuclear multilocus data, to detect mito-nuclear discrepancies derived from hybridization/introgression events 26 .…”
Section: Introductionmentioning
confidence: 99%
“… 2012 ; Jurado-Rivera et al. 2017 ) was also found ( Figure 1 ). Neocaridina heteropoda koreana mitochondrial genome will be utilized to investigate phylogenetic relationships of Neocaridina species.…”
mentioning
confidence: 57%
“…Phylogenetic trees show congruent relationship with (i) placement of Neocaridina within polyphyletic genus Caridina, (ii) polyphyly of genus Typhlatya, and (iii) Typhlatya galapagensis grouping with Halocaridina. However, incongruency of (i) placement of genus Halocaridinides and (ii) phylogenetic relationship among the subfamilies (von Rintelen et al 2012;Jurado-Rivera et al 2017) was also found (Figure 1). Neocaridina heteropoda koreana mitochondrial genome will be utilized to investigate phylogenetic relationships of Neocaridina species.…”
mentioning
confidence: 99%
“…He suggested that hypogeal shrimps could have widespread and probably longstanding populations in submerged as well as emergent rock of the tropical Indo-Pacific that are difficult to sample and thus remain largely unrecorded. However, the current disjunctions observed in the Atyidae are not straightforward and may actually derive from a mixture of both ancient vicariance and recent dispersal (Jurado-Rivera et al 2017, Page et al 2014, Weese et al 2013. In Halocaridinides, the number of localities currently known (Fig.…”
Section: Systematic Accountmentioning
confidence: 99%